Effects of Curcuma longa extracts on mortality and fecundity of Bactrocera zonata (Diptera: Tephritidae) Efeitos dos extratos de Curcuma longa sobre mortalidade e fecundidade de Bactrocera zonata (Diptera: Tephritidae) - Abdul Rauf Siddiqi; Athar Rafi; Falak Naz; Rafique Masih; Iftikhar Ahmad; Ghulam Jilani (Ciência e Agrotecnologia, 2011)
The peach fruit fly, Bactrocera zonata, is a significant pest of fruit and vegetable crops in South East Asia and Pacific region. Ccontrol strategies of fruit flies, relying chiefly on insecticides, have serious environmental consequences, disturbing the agro-ecosystem as well as eliminating natural enemies. This study was oriented at exploring the potential of turmeric, Curcuma longa, extracts to control the peach fruit fly. Freshly emerged female adults of Bactrocera zonata were continuously fed for 16 days on diet containing 1000, 500 and 250 ppm of acetone extract of Curcuma longa separately in laboratory cages. The extract caused 85.00, 66.67 and 56.67 percent mortality at 1000, 500 and 250 ppm respectively. The surviving females were mated and allowed to reproduce on clean guava fruits in separate cages. The inhibition in pupal progeny was 67.90, 60.74 and 51.96 percent in the flies fed on 1000, 500 and 250 ppm, the inhibition observed in adult progeny was 84.68, 79.03 and 67.74 percent, respectively. A mosca do pêssego, Bactrocera zonata, é uma importante praga das frutas e produtos hortícolas no Sudeste Asiático e Pacífico. As estratégias de controle de moscas-das-frutas, que se baseia principalmente no uso de inseticidas, têm consequências ambientais graves, perturbando o agroecossistema, bem como eliminando os inimigos naturais. Este estudo foi orientado a explorar as potencialidades dos extratos de açafrão Curcuma longa para controle de B. zonata. Após a emergência, adultos de fêmeas de B. zonata foram continuamente alimentados, durante 16 dias, com dieta contendo 1000, 500 e 250 ppm de extrato acetônico de C. longa separadamente em gaiolas no laboratório. O extrato causou 85,00, 66,67 e 56,67 % de mortalidade em 1000, 500 e 250 ppm, respectivamente. As fêmeas foram acasaladas e postas para ovipositar separadamente em goiabas dentro das gaiolas. A inibição na progênie pupal foi 67,90, 60,74 e 51,96 % nos insetos alimentados em 1000, 500 e 250 ppm, a inibição observada na progênie adulta foi 84,68, 79,03 e 67,74%, respectivamente.